Penerapan Simple Additive Weighting Dalam Pemilihan Jenis Simpanan Untuk Calon Nasabah - Adiat Pariddudin; Cindy Cesilya (Sekolah Tinggi Ilmu Komputer Binaniaga, 2021)
In the decision-making process that involves several criteria and alternatives, the Simple Additive Weighting (SAW) method is often used as a problem-solving method. Decision making is done by giving weight to each criterion. The criteria used are age, occupation, income and purpose of opening an account. These criteria are what influence decision making. The problem that occurs in determining the decision to choose the best deposit product is that many customers of Bank BNI KCP Pertamina Pusat do not know and are not precise in choosing the type of deposit product to be used. To reduce this inaccuracy, it is necessary to design a decision support system in selecting the best type of savings for prospective customers using the SAW (Simple Additive Weighting) Method because the SAW method is one of the decisions to assess each alternative or predetermined criteria. The results of this assessment are obtained from the top ranking with priority consisting of 4 (four) criteria and sub criteria so that the creation of an adequate Decision Support System (DSS) can help customer service officers in selecting the best savings products for prospective customers of the BNI KCP Pertamina Pusat bank. . The conclusion of this study shows that there are significant changes before development with after development, because it is able to provide accurate decision results.